Osteoblast-specific inactivation of p53 results in locally increased bone formation - Nannan Liao (Public Library of Science (PLoS), 2021)
Inactivation of the tumor suppressor p53 (encoded by the Trp53 gene) is relevant for development and growth of different cancers, including osteosarcoma, a primary bone tumor mostly affecting children and young adolescents. We have previously shown that deficiency of the ribosomal S6 kinase 2 (Rsk2) limits osteosarcoma growth in a transgenic mouse model overexpressing the proto-oncogene c-Fos. Our initial aim for the present study was to address the question, if Rsk2 deficiency would also influence osteosarcoma growth in another mouse model. For that purpose, we took advantage of Trp53fl/fl mice, which were crossed with Runx2Cre transgenic mice in order to inactivate p53 specifically in osteoblast lineage cells. However, since we unexpectedly identified Runx2Cre-mediated recombination also in the thymus, the majority of 6-month-old Trp53fl/fl;Runx2-Cre (thereafter termed Trp53Cre) animals displayed thymic lymphomas, similar to what has been described for Trp53-deficient mice. Since we did not detect osteosarcoma formation at that age, we could not follow our initial aim, but we studied the skeletal phenotype of Trp53Cre mice, with or without additional Rsk2 deficiency. Here we unexpectedly observed that Trp53Cre mice display a unique accumulation of trabecular bone in the midshaft region of the femur and the humerus, consistent with its previously established role as a negative regulator of osteoblastogenesis. Since this local bone mass increase in Trp53Cre mice was significantly reduced by Rsk2 deficiency, we isolated bone marrow cells from the different groups of mice and analyzed their behavior ex vivo. Here we observed a remarkable increase of colony formation, osteogenic differentiation and proliferation in Trp53Cre cultures, which was unaffected by Rsk2 deficiency. Our data thereby confirm a critical and tumorigenesis-independent function of p53 as a key regulator of mesenchymal cell differentiation.